Placement accuracy algorithm for smart street lights - Ishak Z.; Ahmad W.S.H.M.W.; Radzi N.A.M.; Sulaiman S.; Ramli N.E. (Turkiye Klinikleri, 2023)
Errors; Man machine systems; Advanced control systems; Distance analysis; Emerging technologies; GPS Coordinates; Human errors; Light poles; Maintenance work; Placement accuracy; Global positioning system